RETRACTED: Abnormal Mitochondria-Endoplasmic Reticulum Communication Promotes Myocardial Infarction - Cheng, Degang; Zheng, Jia; Hu, Fang; Lv, Wei; Lu, Chengzhi (Frontiers in Physiology, 2021)
Myocardial infarction is characterized by cardiomyocyte death, and can be exacerbated by mitochondrial damage and endoplasmic reticulum injury. In the present study, we investigated whether communication between mitochondria and the endoplasmic reticulum contributes to cardiomyocyte death after myocardial infarction. Our data demonstrated that hypoxia treatment (mimicking myocardial infarction) promoted cardiomyocyte death by inducing the c-Jun N-terminal kinase (JNK) pathway. The activation of JNK under hypoxic conditions was dependent on overproduction of mitochondrial reactive oxygen species (mtROS) in cardiomyocytes, and mitochondrial division was identified as the upstream inducer of mtROS overproduction. Silencing mitochondrial division activators, such as B cell receptor associated protein 31 (BAP31) and mitochondrial fission 1 (Fis1), repressed mitochondrial division, thereby inhibiting mtROS overproduction and preventing JNK-induced cardiomyocyte death under hypoxic conditions. These data revealed that a novel death-inducing mechanism involving the BAP31/Fis1/mtROS/JNK axis promotes hypoxia-induced cardiomyocyte damage. Considering that BAP31 is localized within the endoplasmic reticulum and Fis1 is localized in mitochondria, abnormal mitochondria-endoplasmic reticulum communication may be a useful therapeutic target after myocardial infarction.